Decolorization and degradation potential of enhanced lignocellulolytic enzymes production by Pleurotus eryngii using cherry waste from industry. (29th January 2020) - Akpinar, Merve; Ozturk Urek, Raziye
Abstract: Lignocellulosic wastes accumulate in large quantities and thus cause environmental issues. Cherry waste (CW) of them collected from industry was used as the substrate to increase production of lignocellulolytic enzymes, laccase (Lac), manganese peroxidase (MnP), lignin peroxidase (LiP), carboxymethyl cellulase (CmCase), xylanase, exoglucanase, β‐glucosidase (BGLA), by Pleurotus eryngii . Then, the decolorizations of some azo dyes were examined. The effects of different concentrations of some compounds, such as copper, iron, Tween 80, ammonium nitrate, and manganese, on the productions of lignocellulolytic enzymes were studied depending on incubation period. The maximum productions of lignocellulolytic enzymes were achieved by performing 5.0 g CW and 1, 000 µM Cu 2+, 1, 000 µM Fe 2+, 2.0 g L −1 ammonium nitrate, 180 µM Mn 2+ as the inducers. To the results determined under optimized conditions, 3.61, 4.79, 1.86, 1.15, 2.24, and 2.91‐fold increases were respectively obtained for Lac, MnP, LiP, CMCase, xylanase, and BGLA activities. The chemical changes of dye structure during decolorization by lignocellulolytic enzymes extract containing Lac with decolorization performance as 12.6 ± 0.8% were partially characterized using Fourier transform infrared spectroscopy. This study is important in terms of dye decolorization and degradation by achieving the enhancement of the activities of seven lignocellulolytic enzymes using various inductors. Abstract : The graphical abstract showed the main map of this study using P. eryngii as a biological source and cherry waste as a solid material of SSF. P. eryngii was prepared on agar plates for inoculation, then applied to flasks for SSF. Later, the collected flasks were analyzed in all enzyme activities on each cultivation days.